Gouache gilding on lead and wood objects studied by multivariate and graph analyses applied to XRF spectra. (April 2022) - Brocchieri, Jessica; Scialla, Elvira; Manzone, Anna; Oreste Graziano, Giuseppe; Sabbarese, Carlo
Highlights: Characterization of the gouache gilding technique of cultural heritage objects. X ray fluorescence analysis of gilded lead objects and gilded wooden objects. Application of multivariate analysis and graph theory on X Ray Fluorescence spectra. Classification and discrimination of gouache gilded objects from Royal Palace of Caserta. Thickness estimation of the gold layer and preparatory layer by X-ray fluorescence lines ratios. Abstract: The characterization of the gouache gilding carried out on fifteen objects of the Royal Palace in Caserta (1752) was performed using XRF spectra. The matrix of the spectra was analyzed by multivariate and graph analyses. The analytical methods PCA, HCA, CA and GA were effectively used to highlight the division of the objects into three main clusters: lead objects, wood objects and objects restored with porporina . Among them, graph analysis proved to be the most detailed method for their discrimination and classification. The thickness of the gold layer and the preparatory layer of the objects were also evaluated using ratios of the main intensities of the fluorescence lines. This study is a fundamental starting point to broaden our knowledge of artworks and to objectively evaluate their artistic and historical value.